2021
DOI: 10.1167/iovs.62.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Detailed Photoreceptor Structure and Retinal Sensitivity in Diabetic Macular Ischemia Using Adaptive Optics-OCT and Microperimetry

Abstract: Purpose The purpose of this study was to assess density and morphology of cone photoreceptors (PRs) and corresponding retinal sensitivity in ischemic compared to nonischemic retinal capillary areas of diabetic eyes using adaptive optics optical coherence tomography (AO-OCT) and microperimetry (MP). Methods In this cross-sectional, observational study five eyes of four patients (2 eyes with proliferative diabetic retinopathy (DR) and 3 eyes moderate nonproliferative DR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In previous study, it was also found that in patients with DR, the macular mean sensitivity decreased along with a decrease in DCP vessel perfusion. 21 Using adaptive optics scanning laser ophthalmoscopy, it was also found that PR heterogeneity packing index had a significant correlation with DCP vessel density in patients with DR. 22 This study had several limitations. This study only followed up patients with PDR after vitrectomy, and there was a lack of studies on non-proliferative diabetic retinopathy and non-DR patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous study, it was also found that in patients with DR, the macular mean sensitivity decreased along with a decrease in DCP vessel perfusion. 21 Using adaptive optics scanning laser ophthalmoscopy, it was also found that PR heterogeneity packing index had a significant correlation with DCP vessel density in patients with DR. 22 This study had several limitations. This study only followed up patients with PDR after vitrectomy, and there was a lack of studies on non-proliferative diabetic retinopathy and non-DR patients.…”
Section: Discussionmentioning
confidence: 97%
“…In previous study, it was also found that in patients with DR, the macular mean sensitivity decreased along with a decrease in DCP vessel perfusion. 21 Using adaptive optics scanning laser ophthalmoscopy, it was also found that PR heterogeneity packing index had a significant correlation with DCP vessel density in patients with DR. 22…”
Section: Discussionmentioning
confidence: 97%
“…Photoreceptor integrity and retinal sensitivity assessed by microperimetry are closely linked and can be assessed using the combination of adaptive optics OCT and microperimetry [ 27 , 28 ]. Since the RPE is strongly involved in the nourishment of photoreceptors, it becomes apparent that increased degeneration of the RPE might ultimately result in reduced photoreceptor function [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, non-perfusion in the DCP correlates with microstructural changes indicating photoreceptor damage, such as ellipsoid zone and external limiting membrane disruption and outer nuclear layer focal thinning ( 47 ). Recent studies involving adaptive optics-OCT unveiled severely altered morphology and density of cone photoreceptors in areas of CNP, together with a strong reduction of retinal sensitivity ( 48 ).…”
Section: The Role Of Capillary Non-perfusionmentioning
confidence: 99%